Assessment of investment in electric buses: A case study of a public transport company - Fabianova Jana (De Gruyter, 2021)
This case study presents an assessment of the efficiency and risk of the vehicle fleet renewal in the public transport company. The investment project is solved in two alternatives. The first alternative consists of vehicle replacement by only electric buses. In the second alternative, a combination of electric buses and CNG buses is considered. Assessment of the economic efficiency of the investment project is based on the net present value (NPV). Due to lower initial and ongoing capital expenditures, the second alternative is more cost-effective than the first one although the profitability of the investment project is low. Within risk assessment, sensitivity analysis points out the subsidy and personal costs as the risk factors influencing variance of NPV the most. Finally, the effectiveness of the investment project is assessed at different levels of the use of financial support from EU funds and the state budget. In that case, even a low level of financial support significantly increased the profitability of the project.